2004
DOI: 10.1021/ja048038p
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Silicon Clusters in the Presence of Water:  A First Principles Theoretical Analysis

Abstract: We investigate the impact of water on the optical absorption of prototypical silicon clusters. Our clusters contain 5 silicon atoms, tetrahedrally coordinated and passivated with either hydrogen or oxygen. We approach this complex problem by assessing the contributions of three factors: chemical reactivity, thermal equilibration, and dielectric screening. We find that the silanone (Si=O) functional group is not chemically stable in the presence of water and exclude this as a source of significant red shift in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 53 publications
5
27
1
Order By: Relevance
“…Within Ziegler's sum model for restricted Hartree-Fock states [25], the error incurred by adopting this mixed-state approach is equal to half the singlet-triplet splitting. This error is typically 0.1-0.2 eV in group-IV nanostructures of this size [26], which is small compared with the optical gaps. Previous QMC calculations of the optical gaps of Si nanoparticles [14] using this approach were shown to be in excellent agreement with GW -Bethe-Salpeter-equation (GW -BSE) calculations of the true singlet excitation energies.…”
mentioning
confidence: 89%
“…Within Ziegler's sum model for restricted Hartree-Fock states [25], the error incurred by adopting this mixed-state approach is equal to half the singlet-triplet splitting. This error is typically 0.1-0.2 eV in group-IV nanostructures of this size [26], which is small compared with the optical gaps. Previous QMC calculations of the optical gaps of Si nanoparticles [14] using this approach were shown to be in excellent agreement with GW -Bethe-Salpeter-equation (GW -BSE) calculations of the true singlet excitation energies.…”
mentioning
confidence: 89%
“…In contrast to a great deal of theoretical studies 24–34 on the energy gap or absorption energy, studies on the emission gap are rather scarce, largely due to the lack of an efficient excited‐state (ES) geometric optimization method. However, a clear understanding of the excited state properties and its dynamics is of utmost necessity as the light emission properties of silicon nanoparticles is intimately related to it.…”
Section: Structure–(optical) Property Relationship: a Simple Model mentioning
confidence: 99%
“…The metal atom in the Si n cluster stabilizes the pure Si cluster. Beck 11,12,13,14). Further analysis revealed that Si n cluster with endohedral metal atom impurities are characterized by enhanced stability, strong size selectively, and a large energy gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO).…”
Section: Introductionmentioning
confidence: 99%